2021
DOI: 10.1111/ijfs.15041
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a novel laminarinase from Microbulbifer sp. ALW1 and the antioxidant activity of its hydrolysates

Abstract: Laminarin and its derived oligosaccharides have diverse bioactivities. The b-1,3-glucanase in marine bacteria can be employed as a tool to digest laminarin in the cell wall of brown algae. Here, we cloned, expressed and characterised a b-1,3-glucanase (laminarinase), MaLamNA, from the previously characterised marine bacterium Microbulbifer sp. ALW1, phylogenetically distinct from the glycoside hydrolase families of characterised laminarinases. The recombinant laminarinase was heterologously expressed and purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…Hydrolases in algae-lysing bacteria can dissolve the cell wall of cyanobacteria and kill the algal cells. Hu et al [ 21 ] found a β1,3-glucanase in the marine bacteria Microbulbifer sp. ALW1 can digest laminarin in the cell wall of brown algae.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolases in algae-lysing bacteria can dissolve the cell wall of cyanobacteria and kill the algal cells. Hu et al [ 21 ] found a β1,3-glucanase in the marine bacteria Microbulbifer sp. ALW1 can digest laminarin in the cell wall of brown algae.…”
Section: Discussionmentioning
confidence: 99%
“…The reducing sugars produced during incubation with ALW1 cells were probably utilised by the strain to support the cell growth. The ALW1 cells or its related enzymes could be used to produce oligosaccharides or monosaccharides (Hu et al 2021 ; Jiang et al 2019 ; Li et al 2022b ; Zhu et al 2016b ). Algal oligosaccharides have antitumour, antihypertensive, antioxidant and whitening effects, and they also can suppress IgE production, improve the intestinal microflora, and promote cell proliferation and plant growth (Chen et al 2019 ; Jagtap et al 2022 ; Zhu et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The polysaccharides tested included alginate, laminarin, fucoidan and cellulose. Enzyme activity was determined following the procedures of the 3,5-dinitrosalicylic acid (DNS) method (Hu et al 2021 ; Jiang et al 2019 ; Li et al 2021a ; Miller 1959 ). The reaction was initiated by adding 2 mL of the crude enzymes to 2 mL of 5 mg/mL individual substrate in 50 mM Na 2 HPO 4 -NaH 2 PO 4 (pH 7.0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These polysaccharides are structurally atypical compared to terrestrial glycans and are resistant to gastric acid, gastrointestinal absorption and host digestive enzymes [7]. In addition, enzymatic hydrolysis of seaweed-derived carbohydrates and proteins promotes changes in physicochemical properties and enhances the efficacy of bioactivities such as antioxidant activity [8,9]. Marine algae polysaccharides can be used as prebiotics for gut microbiota, which partially degrade them into other bioactive compounds, such as oligosaccharides and short chain fatty acids (SCFAs) acting as food sources for these organisms and allowing them to proliferate [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%